CFD assessment of a solar honeycomb (SHC) façade element with integrated PV cells. (August 2015) - Brandl, D.; Mach, T.; Kaltenecker, P.; Sterrer, R.; Neururer, C.; Treberspurg, M.; Hochenauer, C.
Highlights: Thermal analysis of a solar honeycomb façade element with a 3D CFD model. Laboratory experiments were used for the validation of the simulations. Different PV configurations at the solar honey comb's front glass were evaluated. Thermal behaviour was also analysed for summer and winter climate conditions. Abstract: The thermal behaviour and air flow characteristic for a solar honeycomb (SHC) façade element at different PV cell configurations was analysed in order to evaluate the thermal and ventilation performance as well as the electrical output. The base construction of this façade prototype inherited from the base façade element "GAP-Skin", which is a development of the company "Gap 3 solutions GmbH". The aim was to find a PV cell configuration which shows the best ratio between the thermal behaviour of the SHC façade and the electrical output of the PV array. Three-dimensional CFD simulations were performed and compared with measurement data from a laboratory experiment. In order to do this, a test stand was built with a 1 × 1 m SHC façade element and a solar simulator. The CFD models contained a detailed radiation model to take solar and thermal radiation into account. The numerical results from the developed models correlated well to a large extent with the measured data. Furthermore, this study obtained the thermal behaviour of the SHC façade element in summer and winter climate conditions in the temperate zone, considering different solar absorption characteristics of the SHC at different solar angles.